1987
DOI: 10.1227/00006123-198703000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Cerebrospinal Fluid Pulse Wave Spectrum Associated with Raised Intracranial Pressure

Abstract: The frequency spectrum of the cerebrospinal fluid (CSF) pulse and the amplitude transfer function between arterial and CSF pressures were measured from the cisterna magna of anesthetized, artificially ventilated cats when the intracranial pressure (ICP) was raised by saline infusion. The spectrum of CSF pulsation was composed of a fundamental and three higher harmonic waves. The amplitude and the amplitude transfer function of each spectral component revealed significant positive correlation with ICP and negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…30 Pulse transmission between arterial pressure and mean ICP has been investigated by various groups. [31][32][33] It depends upon assumptions about the linearity of the transmission model. Such assumptions are probably unrealistic particularly in pathological circumstances.…”
Section: Other Methods Of Icp Analysismentioning
confidence: 99%
“…30 Pulse transmission between arterial pressure and mean ICP has been investigated by various groups. [31][32][33] It depends upon assumptions about the linearity of the transmission model. Such assumptions are probably unrealistic particularly in pathological circumstances.…”
Section: Other Methods Of Icp Analysismentioning
confidence: 99%
“…Measuring the fundamental harmonics instead of the full shape of the AMP implies some loss of information. However, similar techniques proved to be useful in waveform analysis of ICP or transcranial Doppler for assessing critical closing pressure (1,32). Generally, good correlation between the AMP first harmonic and the peak-to-peak amplitude is reported within or between patients (19).…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
“…For example, it has been shown that variations of the ICP pulse morphology are linked to the development of intracranial hypertension [4,5] and cerebral vasospasm [6], acute changes in the cerebral blood carbon dioxide (CO 2 ) levels [7,8], changes in the craniospinal compliance [9], decreased cerebral blood flow [10], and elevated ICP [11]. Therefore, the extraction of morphological features may provide insight to monitor and to understand ICP in an automatic fashion with the ultimate goal of improving the treatment of pathophysiological intracranial and cerebrovascular dynamics.…”
Section: Introductionmentioning
confidence: 99%